2012
DOI: 10.1002/stem.1080
|View full text |Cite
|
Sign up to set email alerts
|

Neurotrophic Bone Marrow Cellular Nests Prevent Spinal Motoneuron Degeneration in Amyotrophic Lateral Sclerosis Patients: A Pilot Safety Study

Abstract: The objective of this article is to assess the safety of intraspinal infusion of autologous bone marrow mononuclear cells (BMNCs) and, ultimately, to look for histopathological signs of cellular neurotrophism in amyotrophic lateral sclerosis (ALS) patients. We conducted an open single arm phase I trial. After 6 months observation, autologous BMNCs were infused into the posterior spinal cord funiculus. Safety was the primary endpoint and was defined as the absence of serious transplant-related adverse events. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
68
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(75 citation statements)
references
References 26 publications
4
68
1
Order By: Relevance
“…These confirms and reassure the previous findings by other groups about the safety of the IT infusion of SCs [52,53,[68][69][70]72,77].…”
Section: Safetysupporting
confidence: 92%
See 2 more Smart Citations
“…These confirms and reassure the previous findings by other groups about the safety of the IT infusion of SCs [52,53,[68][69][70]72,77].…”
Section: Safetysupporting
confidence: 92%
“…Our results support the safety of the method and add unique information about the effectiveness of autologous stem cells to treat ALS supporting previous reports that described safety, feasibility and in some cases stop of the functional declination [52,53,[68][69][70]72,77].…”
Section: Alsfrs-rsupporting
confidence: 90%
See 1 more Smart Citation
“…There have been ten studies thus far evaluating the effects of cellular therapy in 203 patients. [24][25][26][27][28][29][30][31][32] These studies have demonstrated beneficial effects on survival, motor function, and in stabilizing the progressive deterioration in the forced vital capacity of ALS patients. Some of the notable results are found in the following studies: 1) Prabhakar et al conducted a pilot study of ten patients receiving adult autologous BMMNCs intrathecal transplantation.…”
Section: Amyotrophic Lateral Sclerosismentioning
confidence: 99%
“…Thus, the authors suggested that slowing of the disease course in these subjects may have been a reflection of the disease phenotype and not the therapy. Another group, in Spain, evaluated 11 patients following injection of autologous bone marrow-derived MSCs into the spinal cord [77,78]. No serious adverse events were reported nor were there any reported changes in the disease course; however, MNs near the areas of grafting showed fewer degenerative signs on histopathology.…”
Section: Bone Marrow-derived Hematopoietic Progenitor Stem Cellsmentioning
confidence: 99%